2024
DOI: 10.1002/mbo3.1400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the polysaccharide capsule and its heptose on the resistance of Campylobacter jejuni to innate immune defenses

Matthew Myles,
Heba Barnawi,
Mahmoud Mahmoudpour
et al.

Abstract: Campylobacter jejuni is a commensal in many animals but causes diarrhea in humans. Its polysaccharide capsule contributes to host colonization and virulence in a strain‐ and model‐specific manner. We investigated if the capsule and its heptose are important for interactions of strain NCTC 11168 with various hosts and their innate immune defenses. We determined that they support bacterial survival in Drosophila melanogaster and enhance virulence in Galleria mellonella. We showed that the capsule had limited ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Strain-to-strain variation in the location of heptose sugars within the CPS has also been observed. For example, in strain 81–176, the heptose moiety is an inherent part of the repeating unit of the CPS, whereas strain 11168 possesses a heptose moiety that branches off from the repeating unit [ 79 ]. Because of this, the heptose synthesis mutants of strain 11168 still possess the CPS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strain-to-strain variation in the location of heptose sugars within the CPS has also been observed. For example, in strain 81–176, the heptose moiety is an inherent part of the repeating unit of the CPS, whereas strain 11168 possesses a heptose moiety that branches off from the repeating unit [ 79 ]. Because of this, the heptose synthesis mutants of strain 11168 still possess the CPS.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the heptose synthesis mutants of strain 11168 still possess the CPS. Myles et al [ 79 ] have recently taken advantage of this fact by using these mutants to elucidate the distinct roles of the CPS and its branching heptose during infection. The study found that the capsule reduced bacterial adherence to and uptake by chicken macrophages, and decreased intracellular survival, whereas the heptose moieties in the CPS had the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation